The handbook of global education policy - Mundy, Karen E. Karen Elizabeth 1962-; Green, Andy 1954-; Lingard, Bob; Verger, Antoni 1975- (Chichester, United Kingdom Malden, Massachusetts John Wiley & Sons, 2016)
"This innovative new handbook offers a comprehensive overview of the ways in which domestic education policy is framed and influenced by global institutions and actors. Surveys current debates about the role of education in a global polity, highlights key transnational policy actors, accessibly introduces research methodologies, and outlines global agendas for education reform. Includes contributions from an international cast of established and emerging scholars at the forefront of the field thoughtfully edited and organized by a team of world-renowned global education policy experts. Each section features a thorough introduction designed to facilitate readers’ understanding of the subsequent material and highlight links to interdisciplinary global policy scholarship. Written in an accessible and engaging style that will appeal to domestic and international policy practitioners, social scientists, and education scholars alike"--
Contents; List of Acronyms; Introduction: The Globalization of Education Policy -- Key Approaches and Debates ; Part I: Education and a Global Polity; Introduction; 1: Educational Policies in the Face of Globalization: Whither the Nation State; 2: World Society and the Globalization of Educational Policy; 3: The Global Diffusion of Education Privatization: Unpacking and Theorizing Policy Adoption; 4: Economic Growth in Developing Countries: The Role of Human Capital; 5: Education, Poverty, and the "Missing Link": The Limits of Human Capital Theory as a Paradigm for Poverty Reduction; 6: Gender and Education in the Global Polity; 7: The Global Educational Reform Movement and Its Impact on Schooling; 8: Global Convergence or Path Dependency: Skill Formation Regimes in the Globalized Economy; Part II: Educational Issues and Challenges; Introduction; 9: Education and Social Cohesion: A Panglossian Global Discourse; 10: Policies for Education in Conflict and Post-Conflict; 11: Human Rights and Education Policy in South Asia; 12: Early Childhood Education and Care in Global Discourses; 13: Education for All 2000-2015: The Influence of Global Interventions and Aid on EFA Achievements; 14: The Politics of Language in Education in a Global Polity; 15: The Global Governance of Teachers' Work; 16: The Global Policy Actors in Education; Introduction; 17: The Historical Evolution and Current Challenges of the United Nations and Global Education Policy-Making; 18: The World Bank and the Global Governance of Education in a Changing World Order; 19: The Changing Organizational and Global Significance of the OECD's Education Work; 20: The Policies that Shaped PISA, and the Policies that PISA Shaped; 21: Dragon and the Tiger Cubs: China-ASEAN Relations in Higher Education; 22: An Analysis of Power in Transnational Advocacy Networks in Eduction; 23: The Business Case for Transnational Corporate Participation, Profits, and Policy-Making in Education; 24: New Global Philanthropy and Philantropic Governance in Education in a Post-2015 World; Part IV: Critical Directions in the Study of Global Education Policy; Introduction; 25: Rational Intentions and Unintended Consequences: On the Interplay between International and National Actors in Educatin Policy; 26: Policy and Administration as Culture: Organizational Sociology and Cross-National Education Trends; 27: Ethnography and the Localization of Global Education Policy; 28: Global Education Policy and the Postmodern Challenge; 29: Policy Responses to the Rise of Asian Higher Eduction: a Postcolonial Analysis; 30: Joined-up Policy: Network Connectivity and Global Education Governance; 31: A Vertical Case Study of Global Policy-Making: Early Grade Literacy in Zambia; 32: Global Indicators and Local Problem Recognition: An exploration into the Statistical Eradication of Teacher Shortage in the Post-Socialist Region; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Education -- International cooperation; Education and state -- United States; Educational change -- Government policy